FRAUD PENTAGON THEORY DALAM PENDEKATAN ANALISIS FRAUDULENT FINANCIAL REPORTING - Ida Sapriani (2021)
This study was conducted to examine the effect of fraud pentagon theory on fraudulent financial reporting. In this study fraud pentagon theory is measured by financial target, external pressure, ineffective monitoring, change in auditor, change in directors, and frequent number of CEO pictures. And the measurement for fraudulent financial reporting is companies who did or did not make a correction its annual report. The population in this study is 105 companies in financial sectors listed in Bursa Efek Indonesia (BEI). From 105 companies, the samples were selected using purposive sampling and consist of 83 companies and 243 annual reports. The hypothesis using in this study was logistic regression model with SPSS 27 with significance level of 5% or 0.05. The result of this test show: 1) financial target influences fraudulent financial reporting; 2) external pressure influences fraudulent financial reporting; 3) ineffective monitoring influences fraudulent financial reporting; 4) change in auditor has no effect fraudulent financial reporting; 5) change in directors has no effect fraudulent financial reporting; and 6) frequent number of CEO's pictures has no effect fraudulent financial reporting. In this study, one of the implication was for the compay, especially the management could get the information about detetction of fraudulent financial reporting.